Estilo das traduções de Sergio Molina de obras de Ernesto Sabato: um estudo de corpora paralelos espanhol / português - Ariel Novodvorski (2013)
This thesis is associated with Corpus-based Translation Studies (CTS) and, in particular, with studies of Style of Translation, understanding style as a textual attribute in the analysis of a parallel corpus of literary texts in the language pair Spanish / Portuguese. The increase in research in CTS has increased in recent decades (LAVIOSA, 2002); however, it is still necessary to define a more precise theoretical and methodological framework, to research the stylistic profiles of translation (SALDANHA, 2011b). On the other hand, as for research in CTS, the representation of Spanish and Portuguese is also sparse, both in the national and the international scenario. Accordingly, this study aims at investigating the stylistic profile of translations between these languages, using different interfaces with theories and establishing a triangulation of data and results obtained in the investigation. Therefore, the thesis combines the identification of text´s aboutness by keyness, understood as textual quality (SCOTT, 2010; STUBBS, 2010; BERBER SARDINE, 2009); the contrastive analysis of the similarities and differences at the lexicogrammatical level, linked to the (sub) categories of discourse presentation (LEECH; SHORT, 2007; SEMINO; SHORT, 2004), and the identification of cultural meanings conveyed in translation, by the use of italics and punctuation (SALDANHA, 2005, 2011c; MAY , 1997) and paratextual elements (GENETTE, 2009). The research corpus consists of three works of the Argentine author Ernesto Sabato, translated into Brazilian Portuguese by Sergio Molina, and it is part of the ESTRA Corpus - Style of Translation, developed in the LETRA / FALE / UFMG laboratory. The methodological procedures make use of concepts from Corpus Linguistics, especially the use of tools and utilities of the program for lexical analysis WordSmith Tools© 5.0 (SCOTT, 2008). Among the results, three semantic fields were identified through keywords analysis, which indicated the existentialist theme in the corpus. It was also identified a more mentalist status of the corpus based on recurrence of the categories of thought presentation (TP). At the lexicogrammatical level, several changes were observed in the translations, particularly in terms of personal, spatio-temporal deixis, indicating a stress on agentivity and a different deictic referencing in translations, in terms of distance / proximity between text and reader. From the explicit interventions observed, changes were noted in the narrative point of view, with implications on the style and probable mental representation of readers in the translated texts.